Vấn đề về ruộng đất và ảnh hưởng của nó đến sự phát triển kinh tế - xã hội ở nông thôn nước ta trong thời kỳ sau Cách mạng Tháng 8-1945 - Nguyễn, Trí Dĩnh (Bộ Giáo dục và Đào tạo, 2013)
Agriculture will take the first and for most part in the socio-economic development strategy of Vietnam until year 2000. To develop agriculture strongly, farming land has a significance of paramount importance . This article reflects the characteristics of farming land situation in Post-revolution period and its impact to rural socio-economic development, to the relationship of production development and farmers life . Basing on this, the author describes some experiences on using farming land in Vietnamese countryside in the past time and gives some recommendations, directions and measures to solve this issue in Vietnam in the coming time.